TRIM21 regulation of IRF-mediated type I interferon signaling in systemic autoimmune diseases - Panlu, Kailai; Wang, Yihan; Zhu, Xinchao; Lin, Zhiting; Fang, Ting; Yao, Xinyi; Xie, Zhimin; Wang, Xinchang (Frontiers in Immunology, 2025)
Dysregulation of type I interferon (IFN-I) signaling has been implicated in the pathogenesis of multiple systemic autoimmune diseases, including systemic lupus erythematosus, Sjögren’s syndrome, and rheumatoid arthritis. Tripartite motif-containing protein 21 (TRIM21) serves as both a major autoantigen and a pivotal E3 ubiquitin ligase. In the IFN-I pathway, TRIM21 plays a dual regulatory role by targeting transcription factors such as interferon regulatory factor 3 (IRF3), interferon regulatory factor 5 (IRF5), and interferon regulatory factor 7 (IRF7) through multiple ubiquitination mechanisms. This duality enables TRIM21 to both activate IFN-I signaling and mediate its negative feedback, thus maintaining immune homeostasis. However, the presence of anti-TRIM21 autoantibodies may impair its ubiquitin ligase function, resulting in persistent activation of the IFN-I pathway and chronic inflammation. This review summarizes the mechanisms by which TRIM21 regulates IRF family members across various tissues and immune contexts, and explores how its dysfunction contributes to tissue-specific inflammatory responses. Furthermore, we evaluate the potential diagnostic and stratification value of anti-Ro52 antibodies and propose TRIM21 as a novel upstream therapeutic target to restore interferon balance in autoimmune diseases.